PENGUJIAN NORMA HUKUM KETETAPAN MPR NO. XI/MPR/1998 DALAM HIERARKI PERATURAN PERUNDANG-UNDANGAN - Candra Wijaya, Agus Rasyid (Faculty of Law, University of Muhammadiyah Malang, 2016)
The inclusion of the Indonesian People's Consultative Assembly Provisions in the hierarchy of legislation, as stipulated in Article 7 paragraph (1) of Law No. 12 of 2011 on the Establishment of legislation raises several issues related to the establishment and review of the legislation. The Indonesian People's Consultative Assembly Provision No. XI/MPR/1998 on the Implementation of the State that is clean and free of corruption, collusion and nepotism, is one of these provisions is still valid in the structure of the legal norms of the legislation. The purpose of writing this article is to clarify the direction of legal norms of Indonesian People’s Consultative Assembly Provision No. XI/MPR/1998 in testing hierarchy of legislation in the future.